Molecular dynamics simulation of compression induced phase transformation in Cu1Ni3 alloy. Issue 1 (10th September 2021) - Wei, Sun; Wang, Zhenhua; Chen, Jiuye; Zhao, Huining; Zhou, Qingyu; Zeng, Zhengxuan; Chen, Wenshuo; Guo, Shumin
Abstract: The phase transformation mechanism and transformation path of Cu-Ni alloys is very important to study for their applications in excellent electrical properties and chemical catalysis. In this paper, the effect of compressive strain on the transformation path and mechanism of Cu1 Ni3 alloy is studied by molecular dynamics simulations. The simulation results reveal that the transformation path of alloys is from Fcc-Bcc-Hcp phase to other phase (amorphous state). The simulations not only revealed the processes of atomic displacements and pair correlation function during the transformation, but also elucidated the underlying mechanism of the transformation at the atomic level. The mechanism of phase transformation could be the lattice reconstruction caused by lattice sliding and stretching. The simulation results provide a clear landscape on the transformation mechanism, facilitating our comprehensive understanding on the phase transition in the Cu-Ni system.